THE AQUEOUS GEOCHEMISTRY OF RARE EARTH ELEMENTS: V. APPLICATION OF PHOTOACOUSTIC SPECTROSCOPY TO SPECIATION AT LOW RARE EARTH ELEMENT CONCENTRATIONS - Wood S.A.; Tait C.D.; Janecky D.R.; Constantopoulos T.L. (My University, 1995)
Photoacoustic spectroscopy (PAS) yields information on complexation identical to that obtainable with conventional UV-visible absorption spectroscopy, but is up to three orders of magnitude more sensitive. The applicability of PAS to the study of Er3+ oxalate and hydroxide complexes, at 25°C and 1 bar, has been demonstrated. Spectra can be obtained at concentrations as low as 10-20 μM, and observed spectral changes as a function of pH and oxalate concentration are consistent with the most reliable thermodynamic data available for these systems.